Analisis Yuridis Pemberatan Pidana Terhadap Terpidana Residivis Terorisme - Apricia, Nadira; Hutabarat, Rugun Romaida (Universitas Ekasakti, 2023)
Sentencing does not always have a deterrent effect on the perpetrator. The large number of perpetrators who repeat their crimes is proof that the punishment imposed on them does not have a deterrent effect. There needs to be regulation regarding the repetition of criminal acts, especially regarding serious crimes such as criminal acts of terrorism. Improving criminal penalties for repeat criminals or recidivists can be used as a step to reduce and prevent repeated crimes. This research uses the Muhammad Basri case as an example of a repeat case of criminal acts of terrorism. This research aims to find out how criminal penalties are imposed on terrorist recidivists.